Pooling effects from integrating private and corporate demand in car sharing systems. (May 2023) - Frank, Laura; Walther, Grit
Abstract: Car sharing is often associated with the pooling of private mobility demand. Additional pooling effects by integrating private and corporate mobility demand in one car sharing system have not yet been addressed in research. Against this background, we present a mathematical optimization model to identify pooling effects in terms of fleet size reduction in such integrated systems. Herein, the model considers different system designs, for example, the opportunity for companies to temporarily block company-exclusive subfleets at the company location. Moreover, we regard the trade-off between tactical fleet size and operational relocation effort. In a case study, we apply the methodology to the city of Munich. In particular, we examine the impact of system designs, variation in demand, and heterogeneity of private and corporate mobility demand on pooling effects. Our results show fleet size reductions of up to 35% from integrating private and corporate mobility demand in car sharing systems. Highlights: We analyze an integrated car sharing system for private and corporate users. Companies may temporarily block company-exclusive subfleets. We identify pooling effects in terms of fleet size reduction based on an IP. The model considers the trade-off between fleet size and relocation effort. Our case study in Munich shows fleet size reduction potentials of up to 35%.